2002
DOI: 10.1001/archinte.162.16.1873
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Recurrences

Abstract: Reinfection plays an important role in recurrent TB in a population without the clinical/epidemiological circumstances that are usually assumed to favor it. Reinfection should, thus, be considered as a cause of TB recurrences in a wider context than before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Even in this moderate-incidence setting, for 14 (33%) of these 43 patients, the recurrence isolates were unrelated to the original isolates, and thus, these patients were in fact reinfected. Poor treatment adherence and HIV status were not associated with either relapses or reinfections (481).…”
Section: Applications Of Strain Typing To M Tuberculosis Complex Isomentioning
confidence: 87%
See 1 more Smart Citation
“…Even in this moderate-incidence setting, for 14 (33%) of these 43 patients, the recurrence isolates were unrelated to the original isolates, and thus, these patients were in fact reinfected. Poor treatment adherence and HIV status were not associated with either relapses or reinfections (481).…”
Section: Applications Of Strain Typing To M Tuberculosis Complex Isomentioning
confidence: 87%
“…Here, IS6110-RFLP typing showed that 24 (77%) of 31 recurrences after successful treatment were attributable to reinfection, whereas only 4 (11%) of 37 recurrences after treatment default were reinfections (476). García de Viedma et al performed a similar analysis, investigating recurrent TB among 43 patients in Madrid, Spain, most of whom had been poorly adherent to TB therapy (481). Even in this moderate-incidence setting, for 14 (33%) of these 43 patients, the recurrence isolates were unrelated to the original isolates, and thus, these patients were in fact reinfected.…”
Section: Applications Of Strain Typing To M Tuberculosis Complex Isomentioning
confidence: 99%
“…Evidence suggests that in countries with a low TB burden, TB recurrence is usually caused by relapse [30], whereas in countries with a high TB burden the principle cause is reinfection [31], especially when high levels of HIV infection co-exist [20]. In countries with a medium TB burden (like Uzbekistan), relapse and reinfection are both thought to play a role [32], with their relative contribution depending on the prevalence of epidemiological risk factors and the microbiological features of circulating M . tuberculosis strains.…”
Section: Discussionmentioning
confidence: 99%
“…Since the risk of reinfection (a pre-requisite for a mixed strain infection) is a function of the local prevalence of infectious source cases, mixed infection will be most common in settings with a high disease burden. However, reinfection has also been shown to play an important role in disease dynamics in moderate- [1718] and low-incidence communities [19]; this may reflect the increased importance of local clustering of disease among household and close social contacts in these lower incidence settings [20]. Heterogeneity in the frequency of detection of mixed strain infections between existing studies may also reflect differences in study participant selection, methods of specimen collection and storage [21], and in approaches for laboratory identification of multiple strains [22].…”
Section: Introductionmentioning
confidence: 99%